UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE STEM PADA PEMBELAJARAN REAKSI REDOKS DI KELAS XII.MIPA1 SMAN 1 CIGUGUR - Didi Sunardi (Penerbit Lafadz Jaya, 2021)
The purpose of this study was to improve student learning outcomes in the subject matter of Redox Reaction by using the STEM method in class XII.MIPA1 of SMAN 1 Cigugur, Kuningan Regency. The STEM method is an applied learning method that combines knowledge and skills so that students easily understand learning well and obtain the expected learning outcomes. This research uses Classroom Action Research (CAR) with Kurt Lewin's model in 2 cycles. This research was conducted in class XII.MIPA1 SMAN 1 Cigugur which has 30 students. Data collection techniques used are observation, questionnaires, and tests. Furthermore, the data from the observations and questionnaires were processed using a qualitative approach, while the test data were processed using a quantitative approach. The results showed that the activities of students and teachers were included in the very good category. Student response to learning is very positive. Then student learning outcomes increased from an average value of 65 to 87 with the number of students who met the KKM more than 90%.